Directed technical change and the resource curse - Mads Greaker; Tom-Reiel Heggedal; Knut Einar Rosendahl (Statistics Norway, Research Department, 2022)
The "resource curse" is a potential threat to all countries relying on export income from abundant natural resources such as fossil fuels. The early literature hypothesized that easily accessible natural resources would lead to lack of technological progress. In this article we instead propose that abundance of fossil fuels can lead to the wrong type of technological progress. In order to inquire into our research question, we build a model of a small, open economy having specialized in export of fossil fuels. R&D in fossil fuel extraction technology competes with R&D in clean energy technologies. Moreover, technological progress is path dependent as current R&D within a technology type depends on past R&D within the same type. Finally, global climate policy may reduce the future value of fossil fuel export. We find that global climate policy may either lead to a resource curse or help the country escaping a potential resource curse. The ripeness of the clean energy technologies is essential for the outcomes: If the clean technology level is not too far beyond the fossil fuel technology, a shift to exporting clean energy is optimal independent of global climate policy and climate policy can accelerate this shift. While if the clean technology is far behind, a shift should only happen as a response to global climate policy, and the government should intervene to accelerate this shift.
Keywords: O30; O31; O33; 330; Environment; Directed technological change; Innovation policy; Resource curse